Gendered Corporality and Place in Lynn Nottage's Ruined: A Postcolonial Approach - صالح، حسن محمد (جامعة بغداد - كلية الآداب, 2017)
يتناول هذا البحث كيف أن الكاتبة المسرحية لين نوتاج تناقش في مسرحيتها المحطمة فكرة أن الجسد الأنثوي يتأثر ماهية المكان، ويتبنى البحث مقاربة ما بعد الكولونيالية لدراسة هذه المسرحية التي تمثل أنموذجاً جيداً لبيان كيف أن الجسدانية والمكان ذات أهمية كبيرة لتحديد معنى الهوية، ويضم البحث ثلاثة مباحث، يتناول المبحث الأول عرضاً للعلاقة المرتبطة بين الجسد والمكان. وينظر المبحث الثاني آراء لين نوتاج بشأن مكانة المرأة السوداء وكيف تبين نوتاج العلاقة القوية بين الجسدانية النسونية والمكان، في مسرحيتها المختارة. وأخيراً، يلخص البحث أن نوتاج تحاول غرس روح التغيير في النساء من خلال إظهار الترابط الوثيق بين الجسد والمكان.
This paper is an attempt to examine how Lynn Nottage deals with the female body and it is affected by the place in her play Ruined. It adopts a postcolonial approach to the play which represents a good exemplar to explore how corporality and the place are of great relevance to delineate the sense of identity. The paper comprises three sections. The first section offers an account of how the body and place are related. The second section tackles Nottage‘s views of the black women‘s status, and how she figures out the connection between the female corporality and the place in her chosen play. Finally, the paper concludes that Nottage tries to raise in women a spirit of change though showing the strong link of the female corporality and the place.
Keywords: نوتاج، لين -- المسرحيات الإنجليزية